Harnessing Machine Learning for Predictive Maintenance in IoT-Based Smart Manufacturing Environments - Sarwar, Amna; Ahmed , Usama; Mustafa, Muzzamil; Muzzaffar, Muneeb Ali; Hasan, Muhammad Zulkifl; Hussain, Muhammad Zunnurain (UMT Artificial Intelligence Review, 2024)
Industry 4.0 can be considered as a revolution in the industrial sector changing the reality since anew age of smart manufacturing has been introduced that integrates digital technologies including the Internet of Things (IoT), big data analytics, and machine learning (ML).One of the most unlike abilities in transformation is the application of predictive maintenance approach,that is, MLto improve the productivity and efficiency of manufacturing.The current study aimed to prepare a case for anML-basedtool in order topredict the need for maintenance within the Industry 4.0.The study discussedthe information generation from the sensor quantified by ML algorithms followed by the prediction of the equipment to fail prior to its actual failure.Therefore, it minimizesthe duration of downtime and decreasesthe maintenance costs.Key ML techniques,such as regression analysis, neural networks, and decision trees are evaluated to determine their effectiveness in diagnosing and predicting the equipment anomalies.Moreover, the current study reported anotherkey finding that it summarizes case studies from different industries in which predictive maintenance systems based on ML have been implemented successfully.These systemsreflected the substantial increase in production efficiency alongside significant cost reductions.Subsequently, the study also covered relevant topics pertainingto data quality, capacity of the model,and real-time processing difficulty.Additionally, the study at hand alsoaccentuatedthe role of MLas a revolutionary tool to provide maintenance solutions based on predictive analysis. This promotes Industry 4.0 as a manufacturing paradigm aimedat systematic and efficient processes.